Federation of European Laboratory Animal Science Associations recommendations of best practices for the health management of ruminants and pigs used for scientific and educational purposes. (April 2021) - Berset (Convenor), FELASA Working Group on Farm Animals: Corina Mihaela; Caristo, Maria Emiliana; Ferrara, Fabienne; Hardy, Patrick; Oropeza-Moe, Marianne; Waters, Ryan
Most ruminants and pigs used for scientific and educational aims are bred not for these purposes but in a farm environment. Given the wide range of diseases that these species might have, ensuring that the animals' health status is appropriate can be complex and challenging. The Federation of European Laboratory Animal Science Associations has previously published recommendations for the health monitoring of experimental colonies of pigs (1998) and, respectively, calves, sheep and goats (2000). Unfortunately, the uptake of those recommendations was poor and insufficiently reported in scientific publications. These new recommendations for best practice focus on the main species of ruminants (cattle, sheep and goats) and pigs. They provide general and specific information helpful for designing a health management programme for the suppliers and for the user establishments, as well as guidance on animal procurement. Critical thinking based on the fields of use of the animals is promoted, aiming to help in taking informed decisions rather than establishing an exhaustive exclusion list for pathogens. Implementing the best health and welfare management practices should be done under the guidance of a competent attending veterinarian, with expertise and sufficient authority to take the appropriate action, doubled by excellent communication skills. It is strongly recommended that the user establishment's veterinarian works in close collaboration with the supplier's veterinarian.